(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Bursaphelenchus burgermeisteri sp. n. is described from packaging wood made of Pinus radiata and imported from Japan to Ningbo, China. It is characterized by its body length 830 (689-980) μm in males and 890 (766-1037) μm in females; slim body (a = 38 in females, a = 36 in males); stylet 14 μm long; lateral fi eld with four lines; vulva at 77% (average) of total body length; appearance of a vulval fl ap in lateral view; postuterine branch about 60-70% of the vulva-anus distance; female tail long and conical (c = 17, c’ = 4.3); tapering to a fi nely rounded terminus; spicules 27 μm (average) long, having only weakly developed rostrum and condylus, cross-striped in their central part, almost straight, but ventrally bent in their distal end, giving a ‘walking-stick’ impression; male tail terminus with distinct shovel-shaped or pointed bursa seen in dorso-ventral position; three pairs of ventro-sublateral papillae (one pair adanal, and two pairs postanal just in front of the bursa and adjacent to each other). The combination of four lateral lines, the position of caudal papillae and the unique shape of spicules reveal a close relationship of the new species with Bursaphelenchus africanus, but it can be distinguished from the latter by the ‘walking-stick’ shape of spicules, which are also slightly longer. Due to their special characters, these two species are grouped together as the newly created ‘africanus’ group.